A comparative analysis of the frictional resistance of esthetic orthodontic wires - Juliano PILON; Ana Rosa COSTA; Lourenço CORRER-SOBRINHO; Mário VEDOVELLO FILHO; Heloísa Cristina VALDRIGHI (Universidade Estadual Paulista, 2019)
Abstract Introduction The orthodontic movement is directly influenced by the ability of orthodontic wires to slide through brackets and tubes. Therefore, the main concern during orthodontic movement corresponds to the frictional forces generated at the bracket-orthodontic wire interface. Objective This study aimed to evaluate the frictional resistance of esthetic orthodontic wires. Material and method Fifty test brackets were obtained and divided into five groups (n = 10) based on the type of rectangular orthodontic wire, as follows: conventional metallic wire (Morelli, Brazil) (G1, control group) and esthetic wires (G2, Ortho Organizer; G3, Tecnident; G4, Trianeiro; and G5, TP Orthodontics). The following materials and conditions were used: 0.019 x 0.025-inch wires, ceramic brackets with edgewise prescription, torque and/or angulation of 0°, and 0.022 x 0.028-inch slots. The specimens were tested for their tensile strength using an Instron universal test machine at a speed of 1.0 mm / min and a load cell of 500N. The tensile strength data were analyzed by one-way analysis of variance (ANOVA) followed by Tukey's post-hoc test, with a 5% significance level. Result The frictional resistance (N) of the metallic orthodontic wire (8.07 ± 0.43) was significantly higher than that of the esthetic wires: Ortho Organizer (4.01 ± 0.25), Tecnident (3.87 ± 0.31), Trianeiro (4.47 ± 0.26) and TP Orthodontics (4.49 ± 0.30) (p <0.05), with no significant difference between them (p> 0.05). Conclusion To conclude, the esthetic orthodontic wires tested herein showed less frictional resistance as compared to the conventional metallic wire.